Enhancing Mathematical Problem-Solving Skills through the Development of Mission-Based Puzzle Learning Media in Primary Education - Rahmawati, Nita; Wahyudi, Wahyudi (Journal of Innovation and Research in Primary Education, 2025)
This study aims to develop a mission-based puzzle learning media to enhance elementary school students' problem-solving skills, specifically in understanding the concept of fractions. Mathematics instruction often faces challenges in helping students grasp abstract concepts like fractions, which are considered more difficult than whole numbers. Mission-based puzzles are expected to offer an innovative solution to make learning more engaging and to improve students' critical thinking skills. The development model used in this research is ADDIE (Analysis, Design, Development, Implementation, Evaluation), supplemented by the simplified research and development stages of Borg and Gall as modified by Sukmadinata. The study began with a preliminary investigation, including classroom observations and interviews with teachers to identify the learning needs at SD Negeri Butuh 01. Based on this, a prototype of the mission-based puzzle media was designed with a Problem-Based Learning (PBL) approach. The prototype was validated by subject matter experts, media experts, and instructional design experts, and was tested with fifth-grade students. The results showed that the media effectively enhanced students' problem-solving skills in mathematics, with positive responses to its use. The "Mizzle Math" learning media was validated with excellent results (98%, 96%, and 98% for content, media, and design experts, respectively) and demonstrated a significant improvement in students' pretest and posttest scores, with the average posttest score reaching 80. The evaluation indicated that the mission-based puzzle media effectively teach fractions at SD Negeri Butuh 01 and offer an innovative alternative to enhance student engagement and understanding of mathematics.